2011
DOI: 10.1007/s11199-011-0068-4
|View full text |Cite
|
Sign up to set email alerts
|

Not Always a Straight Path: College Students’ Narratives of Heterosexual Identity Development

Abstract: Research has recently begun to examine heterosexual identity development, providing preliminary evidence of variation within a sexual identity category that has frequently been conceptualized as uniform and unremarkable. The current study sought to classify and describe young adult participants’ narratives on their heterosexual identity development using Worthington et al. (2002) heterosexual identity status model. Participants included 1,051 heterosexually-identified undergraduates (632 women; 419 men) from t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
25
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(27 citation statements)
references
References 39 publications
1
25
0
1
Order By: Relevance
“…This may have occurred because adolescent sexual activity is not a perfect indicator of adolescent Running head: GENDER-TYPED BEHAVIOR AND SEXUAL ORIENTATION 19 sexual orientation. For example, some self-identified nonheterosexual adults recall having other-sex sexual contacts during adolescence (Herdt & Boxer, 1996;Rosario et al, 1996;Savin-Williams, 1998), and some self-identified heterosexual adults recall having same-sex sexual contacts during adolescence (Knight & Hope, 2012;Morgan, 2012;Morgan & Thompson, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…This may have occurred because adolescent sexual activity is not a perfect indicator of adolescent Running head: GENDER-TYPED BEHAVIOR AND SEXUAL ORIENTATION 19 sexual orientation. For example, some self-identified nonheterosexual adults recall having other-sex sexual contacts during adolescence (Herdt & Boxer, 1996;Rosario et al, 1996;Savin-Williams, 1998), and some self-identified heterosexual adults recall having same-sex sexual contacts during adolescence (Knight & Hope, 2012;Morgan, 2012;Morgan & Thompson, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…Building upon Erikson's stage-based model of identity ontogeny, other researchers have examined the development of other aspects of individuals' identities, including racial identities (e.g., Winbush, 1977), ethnic identities (e.g., Umaña-Taylor, Yazedjian, & Bámaca-Gómez, 2004), spiritual identities (e.g., Tate, 2007), sexual minority identities (e.g., Cass, 1984;D'Augelli, 1994;Troiden, 1988), and, more recently, heterosexual identities (e.g., Morgan, 2011). While the various sexual minority identity development models that have been developed in the past thirty years have varied in their foci and the intra-and inter-personal components included, they generally encompass several aspects of individuals' lives, including the psychosocial self, sexual fantasies, sexual actions, and romantic interests (Savin-Williams, 2005).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Worthington, Savoy, Dillon, and Vernaglia () provided a complex picture of the factors affecting the development of a heterosexual identity. Since then, research has expanded to consider variations of heterosexual identity (Morgan, ; Thompson & Morgan, ).…”
Section: Developmental Theories Of Sexual Orientation Identity Develomentioning
confidence: 99%